Engagement with “Reclaiming and renegotiating authenticity through autofiction: Meena Kandasamy’s When I Hit You” by Mengchen Lang - Manni, Massimiliano (Narrative Works, 2025)
It is a telling coincidence that Lang puts up a “defense” for ”biographical autofiction,” which she discusses by way of a literary case study in English, against the thesis propounded by a scholar writing in French at a time when autofiction was still a distinctly francophone phenomenon. In so doing, she is not pedantically importing into anglophone autofiction scholarly problems peculiar to another literary tradition, but tracing some of the repressed definitory anxiety preying on English-speaking scholars to an underlying semantic dilemma. Should autofiction that is not overtly fictional – i.e. non-factual – be dismissed as a lesser, illegitimate variety even in English, where fiction, unlike in French, denotes both the made-up and the novelistic? For a body of work that on the whole either borrows French definitions uncritically or bypasses the need for definitions outright by favouring toothless adjectival forms, the question is the prescient endpoint for the psychotherapy of a scholarly tradition.